A compartive study of mental toughness among the state and national level pistol shooting player - Singh, J. (Asian Journal of Physical Education & Computer Science in Sports, 2018)
Mental toughness is the ability to consistently sustain one`s ideal performance state during adversities in competition performing to one`s potential requires good technique and mental skills. The purpose of the study was to find out the difference between the mental toughness of State and National level Pistol shooting Players. The subjects selected for this study were 30 male Shooters from State level tournament and 30 male Shooters from national level Tournament. Mental Toughness Questionnaire1 (2004) prepared by Alan Goldberg is the most appropriate test because it contains only 30 items and it can be filled up within 3 to 5 minutes. It covers the entire Five Mental Toughness components which are rebound ability, pressure tolerance, concentration, confidence, motivation. It is a reliable questionnaire for measuring mental toughness. To analyze the mental toughness among Shooting players of State and National level 'T' test was applied to find out the significant of mean difference between Pistol shooting players of state and national level. There was significant difference found in players participating in different state and national level tournaments.